Участь українських організацій громадянського суспільства в документуванні вчинених РФ в Україні злочинів проти довкілля - Юрченко, Ольга (Видавництво Львівської політехніки, 2025)
The article is devoted to the study of war crimes against the environment of the Ukraine. The problem of forming certain requirements for the procedure of documenting war crimes against the environment, especially in the conditions of armed conflicts, is raised.
Keywords: war crime; environment; information application; war crimes against the environment